2017
DOI: 10.1038/cddiscovery.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

Malathion increases apoptotic cell death by inducing lysosomal membrane permeabilization in N2a neuroblastoma cells: a model for neurodegeneration in Alzheimer’s disease

Abstract: Malathion is an organophosphate with severe neurotoxic effects. Upon acute exposure, malathion initially enhances cholinergic activity by inhibition of acetylcholinesterase, which is its major pathological mechanism. Malathion also induces non-cholinergic neuronal cell death in neurodegenerative conditions; the associated molecular mechanism is not well-characterized. To investigate the molecular mechanism of malathion-induced cell death, N2a mouse neuroblastoma cells were exposed to malathion and cell death-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Also, in previous studies, genes related to cell cycle and apoptosis were targeted by organophosphate pesticide chlorpyrifos in rat PC12 cells (Slotkin and Seidler, 2012), by diazinon in human NT2 cells (Aluigia et al, 2010), and by malathion in N2a neuroblastoma cells (Venkatesan et al, 2017).…”
Section: Gene Expression Change In Response To Parathionmentioning
confidence: 97%
“…Also, in previous studies, genes related to cell cycle and apoptosis were targeted by organophosphate pesticide chlorpyrifos in rat PC12 cells (Slotkin and Seidler, 2012), by diazinon in human NT2 cells (Aluigia et al, 2010), and by malathion in N2a neuroblastoma cells (Venkatesan et al, 2017).…”
Section: Gene Expression Change In Response To Parathionmentioning
confidence: 97%
“…It was also found that MAL affects brain AChE rats and mice pubs exposed during lactation (da Silva et al 2006;Selmi et al 2012). Although AChE inhibition certainly plays a key role in MAL-induced neurotoxicity, but when alone cannot explain the wide range of neurological signs and symptoms that have been reported (Venkatesan et al 2017). Therefore, different noncholinergic mechanisms have been proposed.…”
Section: Mechanisms Of Malathion-induced Neurotoxicitymentioning
confidence: 99%
“…In Montassar lasram et al study, that designed for investigation the malathion hepatic toxicity and the preventive effect of N-acetylcysteine in rats showed that oxidative stress in NAC treated animals, percent of CD4 + and CD8 + T cells and expression of pro-inflammatory cytokine, have reduced [21]. Parola M et al studied on the molecular mechanism in N2a neuroblastoma cells treated by malathion and showed that malathion in- [22].Gupta J et al study investigating in tea effects on cardiovascular disease and shows that catechins by antioxidant activity can reduce ROS and NADPH and by inducing eNOS improves endothelia dysfunction and decrease in Ang-(2) and by protecting mitochondria from dam-age improved cardiac hypertrophy [23].Malathion stimulated lipid peroxidation on subacute, subchronic and chronic periods. Therefore, especially MDA levels in plasma and GSH-Px and Cu-Zn SOD activities in erythrocytes were significantly changed [24].Consistent with previous studies, treatment with EGCG in our experiment led to enhancement in MDA levels and reduction in GSH content.…”
Section: Discussionmentioning
confidence: 99%